Antistatic polarizer protective base film and preparation method thereof

By coating polyurethane modified polyacrylate emulsion on the surface of the polarizer, the anti-static adhesive layer is formed, and the electrostatic voltage problem caused by the protection base film is solved, efficient anti-static performance and good adhesion are achieved, and the use requirements of the liquid crystal display are met.

CN118562402BActive Publication Date: 2025-03-25扬州博恒新能源材料科技有限公司

Patent Information

Application Number
CN202410962786.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-18
Publication Date
2025-03-25
Estimated Expiration
2044-07-18

AI Technical Summary

Technical Problem

During the transportation and assembly of the polarizer, the high resistance value of the protective base film leads to the generation of electrostatic voltage, which damages the liquid crystal molecules and driving circuits of the liquid crystal display.

Method used

By coating a polyurethane modified polyacrylate emulsion on one side of the polarizer, a glue layer with strong adhesion and good antistatic properties is formed. The emulsion obtains bishydroxy quaternary ammonium salt through amidation reaction and quaternization reaction, and uses it as a chain extender and an antistatic agent to improve the cross-linking density and antistatic properties of the glue layer.

Benefits of technology

The low resistance value of the glue layer (below 1010Ω), significantly reduces the generation of static voltage, protects the component performance of the LCD display, and maintains a tight fit under high temperature and high humidity conditions without degumming or bubbles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present invention relates to the field of optical protective base films, specifically to an antistatic polaroid protective base film and a preparation method thereof. The present invention firstly subject 3-dimethylamino-1-propylamine, 10-undecenoic acid and 1,3-dibromo-2,2-dimethylolpropane to amidation reaction and quaternization reaction in sequence to obtain a dihydroxy quaternary ammonium salt; then polytetrahydrofuran ether glycol 2000 and isophorone diisocyanate are used as raw materials for reaction, dihydroxy quaternary ammonium salt and 1,4-butanediol are used as chain extenders for chain extension reaction, and hydroxyethyl methacrylate is added for end-capping to obtain a polyurethane emulsion; the polyurethane emulsion is mixed with ethyl acrylate, methyl methacrylate and methylenebisacrylamide, and a polyurethane-modified polyacrylate emulsion is prepared by a seed semi-continuous polymerization method; finally, the polyurethane-modified polyacrylate emulsion is coated on the surface of a PET film, and dried to obtain an antistatic polaroid protective base film.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of optical protective base films, in particular to an antistatic polarizer protective base film and a preparation method thereof. Background Art

[0002] Polarizers are polarized light sheets throughout the process and are an important component of LCD imaging. During the transportation and assembly steps of polarizers, in order to avoid misjudgment of optical detection performance due to dust adhesion, a protective base film is usually attached to the surface of the polarizer. After the assembly is completed, the surface protective base film is peeled off.

[0003] Although attaching a protective base film is a simple and feasible method, in the process of tearing off the surface protective base film, due to the high resistance value on the protective base film, static voltage is easily generated. The static voltage is harmful to the liquid crystal molecules of the liquid crystal display and the components such as the driving circuit that controls the liquid crystal display. Therefore, the adhesive layer of the protective base film needs to reach a certain resistance value to reduce the damage to the liquid crystal display caused by the static voltage generated in the process of tearing off the protective base film. For this reason, it is necessary to provide an antistatic polarizer protective base film to solve the above problem. Summary of the invention

[0004] The object of the present invention is to provide an antistatic polarizer protective base film and a preparation method thereof, so as to solve the problems raised in the above background technology.

[0005] In order to solve the above technical problems, the present invention provides the following technical solutions: an antistatic polarizer protective base film and a preparation method thereof, comprising the following steps:

[0006] Step 1:

[0007] 3-dimethylamino-1-propylamine, phosphoric acid and 10-undecenoic acid are mixed, an acid binding agent sodium hydroxide is added to adjust the pH, the mixture is reacted in an oil bath at 130-140°C for 10-12 hours, the intermediate product is dispersed in isopropanol after reduced pressure distillation, 1,3-dibromo-2,2-dimethylolpropane is added, the temperature is raised to 75-85°C in a water bath, the mixture is refluxed for 20-24 hours, the reaction solvent is removed by reduced pressure distillation, and then recrystallized using acetone to obtain a dihydroxy quaternary ammonium salt;

[0008] Step 2:

[0009] After dehydrating polytetramethylene glycol 2000, isophorone diisocyanate is added, dibutyltin dilaurate is used as a catalyst, the temperature is raised to 80-90°C for prepolymerization reaction for 2-3 hours, 1,4-butanediol is added, and the chain extension reaction is carried out at 70-80°C for 2-3 hours; the temperature is lowered to 40-45°C, dihydroxy quaternary ammonium salt is added to continue the chain extension reaction for 1-2 hours, acetone is added to adjust the viscosity of the system, the temperature is raised to 70-80°C after the reaction is completed, hydroxyethyl methacrylate is added to carry out end-capping reaction for 30-60 minutes, acetic acid is added to neutralize after natural cooling, and water is added for emulsification to obtain a polyurethane emulsion;

[0010] Step 3:

[0011] The polyurethane emulsion is mixed with ethyl acrylate, methyl methacrylate and methylenebisacrylamide to obtain a composite emulsion; the composite emulsion is divided into two equal parts, an initiator is added to one of the composite emulsions, the temperature is raised to 70-80°C, and the reaction is kept warm for 60-90 minutes to obtain a seed solution; the other composite emulsion is added to the seed solution and an initiator is added, the temperature is raised to 70-80°C, the reaction is kept warm for 30-60 minutes, and then the initiator is added continuously, the reaction is carried out at 80-85°C for 1-2 hours, and the temperature is lowered to obtain a polyurethane-modified polyacrylate emulsion;

[0012] Step 4:

[0013] The polyurethane modified polyacrylate emulsion is coated on one side of the PET film and baked to form an adhesive layer; the PET film is taken out, and a release film is applied on the surface of the adhesive layer to obtain an antistatic polarizer protective base film.

[0014] Furthermore, in step 1, sodium hydroxide is used to adjust the pH value to 8-8.5.

[0015] Furthermore, in step 1, the amount of phosphoric acid used is 0.5-1% of the total weight of 3-dimethylamino-1-propylamine.

[0016] Furthermore, in step 1, the molar ratio of 3-dimethylamino-1-propylamine, 10-undecenoic acid and 1,3-dibromo-2,2-dimethylolpropane is 2:2:1.

[0017] Furthermore, in step 2, the amounts of the components used, by weight, are 40 to 48 parts of polytetramethylene glycol 2000, 30 to 36 parts of isophorone diisocyanate, 1 to 5 parts of 1,4-butanediol, 8 to 13 parts of dihydroxy quaternary ammonium salt, 5 to 8 parts of acetone, 4 to 6 parts of hydroxyethyl methacrylate, and 2 to 3 parts of acetic acid.

[0018] Furthermore, in step 2, the solid content of the polyurethane emulsion is 65-70%.

[0019] Furthermore, in step 3, the contents of the components in the composite emulsion are, by weight percentage, 55-65% polyurethane emulsion, 20-35% ethyl acrylate, 10-15% methyl methacrylate, and 0.3-1% methylenebisacrylamide.

[0020] Furthermore, in step 3, the total amount of initiator used is 0.5-1.5% of the total weight of the reactants in the composite emulsion.

[0021] Furthermore, in step 4, the baking temperature is 110-120° C., the baking time is 2-5 min, and the thickness of the adhesive layer is 10-15 μm.

[0022] Furthermore, in step 4, the preparation method of the PET film is as follows: the waste PET material generated in the process of producing the PET film is crushed, granulated at 270-280°C, mixed with PET slices, dried and dehydrated, and melt-extruded at 240-270°C, the melt is filtered, the unmelted PET and gel-type PET impurities are removed and then returned to the production line, the molten material is extruded, water-cooled, stretched, pulled, corona-treated, and rolled up, and then cut to obtain a PET film, and the thickness of the PET film is 30-50 μm.

[0023] Compared with the prior art, the beneficial effects achieved by the present invention are as follows: the present invention provides a method for preparing an antistatic polarizer protective base film, specifically, by coating a polyurethane-modified polyacrylate emulsion on one side of the polarizer surface, thereby forming a glue layer with strong adhesion and good antistatic performance. When preparing the polyurethane-modified polyacrylate emulsion, the present invention first subject 3-dimethylamino-1-propylamine, 10-undecenoic acid and 1,3-dibromo-2,2-dimethylolpropane to amidation reaction and quaternization reaction in sequence to obtain a dihydroxy quaternary ammonium salt. The dihydroxy quaternary ammonium salt contains two hydroxyl groups in the molecular formula, so the present invention uses polytetramethylene glycol 2000 and isophorone diisocyanate as raw materials, dihydroxy quaternary ammonium salt and 1,4-butanediol as chain extenders, and finally uses hydroxyethyl methacrylate for end-capping to obtain a polyurethane emulsion.

[0024] Dihydroxy quaternary ammonium salt can be used as a chain extender to participate in the synthesis of polyurethane, and can also be used as an antistatic agent for polyurethane to improve its antistatic properties. Since the molecular formula of dihydroxy quaternary ammonium salt contains carbon-carbon double bonds, using dihydroxy quaternary ammonium salt as a chain extender can also introduce carbon-carbon double bonds into the polyurethane side chain, increase the cross-linking sites between polyurethane and acrylate monomers, and improve the cross-linking density. The molecular formula of dihydroxy quaternary ammonium salt contains a longer carbon chain and has properties similar to those of gemini surfactants, that is, it has both hydrophobic associative ability and hydrophilicity, and can produce a good emulsifying effect in the emulsion. Without the addition of an emulsifier, the composite emulsion after the polyurethane and acrylate monomers are mixed can form a stable core-shell structure, which is conducive to the occurrence of polymerization reactions. The polyurethane modified polyacrylate emulsion is coated on the surface of the PET film to form a glue layer, and the surface resistance of the glue layer is 10 10 Ω or less, with good antistatic effect, dihydroxy quaternary ammonium salt is introduced into the resin adhesive layer through chemical bonds, and there is no precipitation during use. The hydrophobic long chain can also eliminate the problem of poor water resistance of the resin caused by hydrophilicity. The protective base film is attached to the surface of the polarizer, and after high temperature and high humidity treatment, it is tightly attached without bubbles and other phenomena such as the protective film and polarizer falling off.

[0025] It should be noted that in the composite emulsion, the more polyurethane is used, the better. The higher the polyurethane content, the higher the flexible long chain content, the softer and looser the polymerized resin molecules are, which leads to a decrease in the adhesion of the cured adhesive layer. Through continuous experiments, it was found that when the polyurethane emulsion is blended with the acrylate monomer, the amount of the polyurethane emulsion is controlled to be 50-65% of the total weight of the composite emulsion, the comprehensive performance of the adhesive layer is the best, and the prepared antistatic polarizer protective base film can meet the application needs.

[0026] In addition, when preparing the PET film, the present invention crushes and granulates the waste PET material in the preparation process, mixes it with the PET raw material, and then returns it to the production line to prepare the PET film, which effectively improves the utilization rate of the PET raw material and improves the production efficiency of the enterprise. DETAILED DESCRIPTION

[0027] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0028] Materials and sources used in the present invention: PET slices are from China Resources Chemical Materials Technology Co., Ltd., item number CR-8839T; polytetramethylene ether glycol 2000 is from Jining Baiyi Chemical Co., Ltd.; release film is from Hefei Lucky Technology Industry Co., Ltd., model FP-2, thickness 36 μm; the initiator is azobisisobutyronitrile from Shanghai Aladdin Biochemical Technology Co., Ltd.

[0029] Example 1: Preparation of PET film.

[0030] The preparation method of PET film is as follows: the waste PET material generated in the process of PET film production is crushed, granulated at 270°C, mixed with PET slices, dried and dehydrated, and melt-extruded at 260°C, the melt is filtered, unmelted PET and gel-type PET impurities are removed and returned to the production line, the molten material is extruded, water-cooled and formed, and then stretched, pulled, corona-treated, and rolled up, and slit to obtain PET film, and the thickness of the PET film is 38μm.

[0031] The PET films used in the following Examples 2 to 6 and Comparative Examples 1 to 2 are all prepared in Example 1.

[0032] Embodiment 2: An antistatic polarizer protective base film and a preparation method thereof, comprising the following steps:

[0033] Step 1:

[0034] 3-dimethylamino-1-propylamine, phosphoric acid and 10-undecenoic acid are mixed, an acid binding agent sodium hydroxide is added to adjust the pH to 8, the mixture is reacted in an oil bath at 130°C for 10 hours, the intermediate product is dispersed in isopropanol after reduced pressure distillation, 1,3-dibromo-2,2-dimethylolpropane is added, the mixture is heated to 75°C in a water bath, the mixture is refluxed for 20 hours, the reaction solvent is removed by reduced pressure distillation, and then the dihydroxy quaternary ammonium salt is obtained by recrystallization using acetone; wherein the amount of phosphoric acid used is 0.5% of the total weight of 3-dimethylamino-1-propylamine; the molar ratio of 3-dimethylamino-1-propylamine, 10-undecenoic acid and 1,3-dibromo-2,2-dimethylolpropane is 2:2:1;

[0035] Step 2:

[0036] After dehydrating 48g of polytetramethylene glycol 2000, 34g of isophorone diisocyanate was added, dibutyltin dilaurate was used as a catalyst, the temperature was raised to 80°C for prepolymerization reaction for 2h, 2g of 1,4-butanediol was added, and the chain extension reaction was carried out at 70°C for 2h; the temperature was lowered to 40°C, 12g of dihydroxy quaternary ammonium salt was added to continue the chain extension reaction for 1h, 7g of acetone was added to adjust the viscosity of the system, and after the reaction was completed, the temperature was raised to 70°C, 5g of hydroxyethyl methacrylate was added for end-capping reaction for 30min, and then naturally cooled, 3g of acetic acid was added for neutralization, and water was added for emulsification to obtain a polyurethane emulsion with a solid content of 70%;

[0037] Step 3:

[0038] The polyurethane emulsion is mixed with ethyl acrylate, methyl methacrylate and methylenebisacrylamide to obtain a composite emulsion; the composite emulsion is divided into two equal parts, an initiator is added to one of the composite emulsions, the temperature is raised to 70°C, and the temperature is kept for reaction for 60 minutes to obtain a seed solution; another composite emulsion is added to the seed solution and an initiator is added, the temperature is raised to 70°C, the temperature is kept for reaction for 30 minutes, and then the initiator is continuously added, the reaction is carried out at 80°C for 1 hour, and the temperature is lowered to obtain a polyurethane modified polyacrylate emulsion; the content of each component in the composite emulsion is, by weight percentage, 55% polyurethane emulsion, 30% ethyl acrylate, 14.5% methyl methacrylate, and 0.5% methylenebisacrylamide; the total amount of initiator is 0.7% of the total weight of the reactants in the composite emulsion;

[0039] Step 4:

[0040] The polyurethane modified polyacrylate emulsion was coated on one side of the PET film and baked at 110°C for 5 hours to form a glue layer with a thickness of 13 μm; the PET film was taken out, and a release film was applied on the surface of the glue layer to obtain an antistatic polarizer protective base film.

[0041] Embodiment 3: An antistatic polarizer protective base film and a preparation method thereof, comprising the following steps:

[0042] Step 1:

[0043] 3-dimethylamino-1-propylamine, phosphoric acid and 10-undecenoic acid are mixed, an acid binding agent sodium hydroxide is added to adjust the pH to 8.3, the mixture is reacted in an oil bath at 135°C for 11 hours, the intermediate product is dispersed in isopropanol after reduced pressure distillation, 1,3-dibromo-2,2-dimethylolpropane is added, the mixture is heated to 80°C in a water bath, the mixture is refluxed for 22 hours, the reaction solvent is removed by reduced pressure distillation, and then acetone is used for recrystallization to obtain a dihydroxy quaternary ammonium salt; wherein the amount of phosphoric acid used is 0.5% of the total weight of 3-dimethylamino-1-propylamine; the molar ratio of 3-dimethylamino-1-propylamine, 10-undecenoic acid and 1,3-dibromo-2,2-dimethylolpropane is 2:2:1;

[0044] Step 2:

[0045] After dehydrating 48g of polytetramethylene glycol 2000, 34g of isophorone diisocyanate was added, dibutyltin dilaurate was used as a catalyst, the temperature was raised to 85°C for prepolymerization reaction for 2.5h, 2g of 1,4-butanediol was added, and the chain extension reaction was carried out at 75°C for 2.5h; the temperature was lowered to 45°C, 12g of dihydroxy quaternary ammonium salt was added to continue the chain extension reaction for 1.5h, 7g of acetone was added to adjust the viscosity of the system, and after the reaction was completed, the temperature was raised to 75°C, 5g of hydroxyethyl methacrylate was added for end-capping reaction for 45min, and then naturally cooled, 3g of acetic acid was added for neutralization, and water was added for emulsification to obtain a polyurethane emulsion with a solid content of 70%;

[0046] Step 3:

[0047] The polyurethane emulsion is mixed with ethyl acrylate, methyl methacrylate and methylenebisacrylamide to obtain a composite emulsion; the composite emulsion is divided into two equal parts, an initiator is added to one of the composite emulsions, the temperature is raised to 75°C, and the reaction is kept warm for 75 minutes to obtain a seed solution; another composite emulsion is added to the seed solution and an initiator is added, the temperature is raised to 75°C, the reaction is kept warm for 45 minutes, and then the initiator is continued to be added, the reaction is carried out at 85°C for 1.5 hours, and the temperature is lowered to obtain a polyurethane modified polyacrylate emulsion; the content of each component in the composite emulsion is, by weight percentage, 55% polyurethane emulsion, 30% ethyl acrylate, 14.5% methyl methacrylate, and 0.5% methylenebisacrylamide; the total amount of initiator is 0.7% of the total weight of the reactants in the composite emulsion;

[0048] Step 4:

[0049] The polyurethane modified polyacrylate emulsion was coated on one side of the PET film and baked at 115°C for 4 hours to form a glue layer with a thickness of 13 μm; the PET film was taken out, and a release film was applied on the surface of the glue layer to obtain an antistatic polarizer protective base film.

[0050] Embodiment 4: An antistatic polarizer protective base film and a preparation method thereof, comprising the following steps:

[0051] Step 1:

[0052] 3-dimethylamino-1-propylamine, phosphoric acid and 10-undecenoic acid are mixed, and an acid-binding agent, sodium hydroxide, is added to adjust the pH to 8.5, and the mixture is reacted in an oil bath at 140°C for 12 hours. After reduced pressure distillation, the intermediate product is dispersed in isopropanol, and 1,3-dibromo-2,2-dimethylolpropane is added. The mixture is heated to 85°C in a water bath, and after reflux reaction for 24 hours, the reaction solvent is removed by reduced pressure distillation, and then acetone is used for recrystallization to obtain a dihydroxy quaternary ammonium salt; wherein the amount of phosphoric acid used is 0.5% of the total weight of 3-dimethylamino-1-propylamine; and the molar ratio of 3-dimethylamino-1-propylamine, 10-undecenoic acid and 1,3-dibromo-2,2-dimethylolpropane is 2:2:1;

[0053] Step 2:

[0054] After dehydrating 48g of polytetramethylene glycol 2000, 34g of isophorone diisocyanate was added, dibutyltin dilaurate was used as a catalyst, the temperature was raised to 90°C for prepolymerization reaction for 3h, 2g of 1,4-butanediol was added, and the chain extension reaction was carried out at 80°C for 3h; the temperature was lowered to 45°C, 12g of dihydroxy quaternary ammonium salt was added to continue the chain extension reaction for 2h, 7g of acetone was added to adjust the viscosity of the system, and after the reaction was completed, the temperature was raised to 80°C, 5g of hydroxyethyl methacrylate was added for end-capping reaction for 60min, and then naturally cooled, 3g of acetic acid was added for neutralization, and water was added for emulsification to obtain a polyurethane emulsion with a solid content of 70%;

[0055] Step 3:

[0056] The polyurethane emulsion is mixed with ethyl acrylate, methyl methacrylate and methylenebisacrylamide to obtain a composite emulsion; the composite emulsion is divided into two equal parts, an initiator is added to one of the composite emulsions, the temperature is raised to 80°C, and the reaction is kept warm for 90 minutes to obtain a seed solution; the other composite emulsion is added to the seed solution and an initiator is added, the temperature is raised to 80°C, the reaction is kept warm for 60 minutes, and then the initiator is continuously added, the reaction is carried out at 85°C for 2 hours, and the temperature is lowered to obtain a polyurethane modified polyacrylate emulsion; the content of each component in the composite emulsion is, by weight percentage, 55% polyurethane emulsion, 30% ethyl acrylate, 14.5% methyl methacrylate, and 0.5% methylenebisacrylamide; the total amount of initiator is 0.7% of the total weight of the reactants in the composite emulsion;

[0057] Step 4:

[0058] The polyurethane modified polyacrylate emulsion was coated on one side of the PET film and baked at 120°C for 3 hours to form a glue layer with a thickness of 13 μm; the PET film was taken out, and a release film was applied on the surface of the glue layer to obtain an antistatic polarizer protective base film.

[0059] Embodiment 5: An antistatic polarizer protective base film and a preparation method thereof, comprising the following steps:

[0060] Step 1:

[0061] 3-dimethylamino-1-propylamine, phosphoric acid and 10-undecenoic acid are mixed, and an acid-binding agent, sodium hydroxide, is added to adjust the pH to 8.5, and the mixture is reacted in an oil bath at 140°C for 12 hours. After reduced pressure distillation, the intermediate product is dispersed in isopropanol, and 1,3-dibromo-2,2-dimethylolpropane is added. The mixture is heated to 85°C in a water bath, and after reflux reaction for 24 hours, the reaction solvent is removed by reduced pressure distillation, and then acetone is used for recrystallization to obtain a dihydroxy quaternary ammonium salt; wherein the amount of phosphoric acid used is 0.5% of the total weight of 3-dimethylamino-1-propylamine; and the molar ratio of 3-dimethylamino-1-propylamine, 10-undecenoic acid and 1,3-dibromo-2,2-dimethylolpropane is 2:2:1;

[0062] Step 2:

[0063] After dehydrating 48g of polytetramethylene glycol 2000, 34g of isophorone diisocyanate was added, dibutyltin dilaurate was used as a catalyst, the temperature was raised to 90°C for prepolymerization reaction for 3h, 2g of 1,4-butanediol was added, and the chain extension reaction was carried out at 80°C for 3h; the temperature was lowered to 45°C, 12g of dihydroxy quaternary ammonium salt was added to continue the chain extension reaction for 2h, 7g of acetone was added to adjust the viscosity of the system, and after the reaction was completed, the temperature was raised to 80°C, 5g of hydroxyethyl methacrylate was added for end-capping reaction for 60min, and then naturally cooled, 3g of acetic acid was added for neutralization, and water was added for emulsification to obtain a polyurethane emulsion with a solid content of 70%;

[0064] Step 3:

[0065] The polyurethane emulsion is mixed with ethyl acrylate, methyl methacrylate and methylenebisacrylamide to obtain a composite emulsion; the composite emulsion is divided into two equal parts, an initiator is added to one of the composite emulsions, the temperature is raised to 80°C, and the reaction is kept warm for 90 minutes to obtain a seed solution; another composite emulsion is added to the seed solution and an initiator is added, the temperature is raised to 80°C, the reaction is kept warm for 60 minutes, and then the initiator is added continuously, the reaction is carried out at 85°C for 2 hours, and the temperature is lowered to obtain a polyurethane modified polyacrylate emulsion; the content of each component in the composite emulsion is, by weight percentage, 65% polyurethane emulsion, 20% ethyl acrylate, 14.5% methyl methacrylate, and 0.5% methylenebisacrylamide; the total amount of initiator is 0.7% of the total weight of the reactants in the composite emulsion;

[0066] Step 4:

[0067] The polyurethane modified polyacrylate emulsion was coated on one side of the PET film and baked at 120°C for 3 hours to form a glue layer with a thickness of 13 μm; the PET film was taken out, and a release film was applied on the surface of the glue layer to obtain an antistatic polarizer protective base film.

[0068] Comparative Example 1: The chain extender dihydroxy quaternary ammonium salt was replaced with 1,4-butanediol to prepare a polyurethane emulsion, and the other parameters were the same as those in Example 2.

[0069] Step 1:

[0070] After dehydrating 48g of polytetramethylene glycol 2000, 34g of isophorone diisocyanate was added, dibutyltin dilaurate was used as a catalyst, the temperature was raised to 80°C for prepolymerization reaction for 2h, 14g of 1,4-butanediol was added, and the chain extension reaction was carried out at 70°C for 2h; after the reaction was completed, 7g of acetone was added to adjust the viscosity of the system, the temperature was raised to 70°C, 5g of hydroxyethyl methacrylate was added for end-capping reaction for 30min, and then naturally cooled, 3g of acetic acid was added for neutralization, and water was added for emulsification to obtain a polyurethane emulsion with a solid content of 70%;

[0071] Step 2:

[0072] The polyurethane emulsion is mixed with ethyl acrylate, methyl methacrylate and methylenebisacrylamide to obtain a composite emulsion; the composite emulsion is divided into two equal parts, an initiator is added to one of the composite emulsions, the temperature is raised to 70°C, and the temperature is kept for reaction for 60 minutes to obtain a seed solution; another composite emulsion is added to the seed solution and an initiator is added, the temperature is raised to 70°C, the temperature is kept for reaction for 30 minutes, and then the initiator is continuously added, the reaction is carried out at 80°C for 1 hour, and the temperature is lowered to obtain a polyurethane modified polyacrylate emulsion; the content of each component in the composite emulsion is, by weight percentage, 55% polyurethane emulsion, 30% ethyl acrylate, 14.5% methyl methacrylate, and 0.5% methylenebisacrylamide; the total amount of initiator is 0.7% of the total weight of the reactants in the composite emulsion;

[0073] Step 3:

[0074] The polyurethane modified polyacrylate emulsion was coated on one side of the PET film and baked at 110°C for 5 hours to form a glue layer with a thickness of 13 μm; the PET film was taken out, and a release film was applied on the surface of the glue layer to obtain an antistatic polarizer protective base film.

[0075] Comparative Example 2: The amount of polyurethane emulsion in the composite emulsion was increased, and the other parameters were the same as those in Example 3.

[0076] Step 1:

[0077] 3-dimethylamino-1-propylamine, phosphoric acid and 10-undecenoic acid are mixed, an acid binding agent sodium hydroxide is added to adjust the pH to 8.3, the mixture is reacted in an oil bath at 135°C for 11 hours, the intermediate product is dispersed in isopropanol after reduced pressure distillation, 1,3-dibromo-2,2-dimethylolpropane is added, the mixture is heated to 80°C in a water bath, the mixture is refluxed for 22 hours, the reaction solvent is removed by reduced pressure distillation, and then acetone is used for recrystallization to obtain a dihydroxy quaternary ammonium salt; wherein the amount of phosphoric acid used is 0.5% of the total weight of 3-dimethylamino-1-propylamine; the molar ratio of 3-dimethylamino-1-propylamine, 10-undecenoic acid and 1,3-dibromo-2,2-dimethylolpropane is 2:2:1;

[0078] Step 2:

[0079] After dehydrating 48g of polytetramethylene glycol 2000, 34g of isophorone diisocyanate was added, dibutyltin dilaurate was used as a catalyst, the temperature was raised to 85°C for prepolymerization reaction for 2.5h, 2g of 1,4-butanediol was added, and the chain extension reaction was carried out at 75°C for 2.5h; the temperature was lowered to 45°C, 12g of dihydroxy quaternary ammonium salt was added to continue the chain extension reaction for 1.5h, 7g of acetone was added to adjust the viscosity of the system, and after the reaction was completed, the temperature was raised to 75°C, 5g of hydroxyethyl methacrylate was added for end-capping reaction for 45min, and then naturally cooled, 3g of acetic acid was added for neutralization, and water was added for emulsification to obtain a polyurethane emulsion with a solid content of 70%;

[0080] Step 3:

[0081] The polyurethane emulsion is mixed with ethyl acrylate, methyl methacrylate and methylenebisacrylamide to obtain a composite emulsion; the composite emulsion is divided into two equal parts, an initiator is added to one of the composite emulsions, the temperature is raised to 75°C, and the reaction is kept warm for 75 minutes to obtain a seed solution; the other composite emulsion is added to the seed solution and an initiator is added, the temperature is raised to 75°C, the reaction is kept warm for 45 minutes, and then the initiator is continued to be added, the reaction is carried out at 85°C for 1.5 hours, and the temperature is lowered to obtain a polyurethane modified polyacrylate emulsion; the content of each component in the composite emulsion is, by weight percentage, 75% polyurethane emulsion, 16% ethyl acrylate, 8.5% methyl methacrylate, and 0.5% methylenebisacrylamide; the total amount of initiator is 0.7% of the total weight of the reactants in the composite emulsion;

[0082] Step 4:

[0083] The polyurethane modified polyacrylate emulsion was coated on one side of the PET film and baked at 115°C for 4 hours to form a glue layer with a thickness of 13 μm; the PET film was taken out, and a release film was applied on the surface of the glue layer to obtain an antistatic polarizer protective base film.

[0084] experiment:

[0085] The performance of the polarizer protective base films prepared in Examples 2 to 5 and Comparative Examples 1 to 2 was tested, and the experimental results are shown in the following table.

[0086] Light transmittance and haze test: refer to standard GB / T2410-2008, tear off the release film on the surface of the sample, and use a haze meter to measure the light transmittance (T) and haze (H);

[0087] Peel force test: Cut the protective base film into 300mm×25mm size, tear off the release film, and stick the protective base film on the surface of the polarizer. Use an electronic universal testing machine to test the peel force. The test angle is 180° and the tensile speed is 300mm / min.

[0088] Adhesive layer resistance test: Cut the protective base film into 12mm×12mm size, tear off the release film, and test the adhesive surface resistance on a high resistance meter.

[0089] High temperature and high humidity test: Cut the protective base film into a size of 150mm×25mm, tear off the release film, and stick the protective base film adhesive layer on the surface of the polarizer. After placing it at 100℃ and 90% humidity for 12 hours, observe whether the protective base film has wrinkles, debonding, or bubbles on the surface of the polarizer. If not, the high temperature and high humidity resistance is good, which is recorded as good; otherwise, it is recorded as bad.

[0090]

[0091] Conclusion: The data in Examples 2 to 5 and Comparative Examples 1 to 2 show that the polarizer protective base film prepared by the present invention has good optical properties and high light transmittance; the resistance value of the adhesive layer is between 10 10 Ω or less, and has antistatic effect; the adhesive force between the polarizer protective base film glue layer and the polarizer is strong, and under the high temperature and high humidity test environment, the protective base film and the polarizer are tightly attached, without bubbles, bulging, degumming and other phenomena, meeting the use requirements. The data of Example 2 and Comparative Example 1 show that the addition of dihydroxy quaternary ammonium salt can effectively improve the antistatic performance, and the adhesion effect of the glue layer is better; the data of Example 3 and Comparative Example 2 show that the performance of the glue layer deteriorates when the content of polyurethane in the mixed emulsion is increased, resulting in the antistatic polarizer failing to meet the application requirements.

[0092] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing an antistatic polarizer protective base film, characterized in that: The following steps are involved: Step 1: 3-dimethylamino-1-propylamine, phosphoric acid and 10-undecenoic acid are mixed, an acid-binding agent sodium hydroxide is added to adjust the pH, the mixture is reacted in an oil bath at 130-140° C. for 10-12 hours, the intermediate product is dispersed in isopropanol after reduced pressure distillation, 1,3-dibromo-2,2-dimethylolpropane is added, the temperature is raised to 75-85° C. in a water bath, the mixture is refluxed for 20-24 hours, the reaction solvent is removed by reduced pressure distillation, and then the dihydroxy quaternary ammonium salt is obtained by recrystallization using acetone; Step 2: After dehydrating polytetramethylene glycol 2000, isophorone diisocyanate is added, dibutyltin dilaurate is used as a catalyst, the temperature is raised to 80-90°C for prepolymerization reaction for 2-3 hours, 1,4-butanediol is added, and the chain extension reaction is carried out at 70-80°C for 2-3 hours; the temperature is lowered to 40-45°C, dihydroxy quaternary ammonium salt is added to continue the chain extension reaction for 1-2 hours, acetone is added to adjust the viscosity of the system, the temperature is raised to 70-80°C after the reaction is completed, hydroxyethyl methacrylate is added to carry out end-capping reaction for 30-60 minutes, acetic acid is added to neutralize after natural cooling, and water is added for emulsification to obtain a polyurethane emulsion; wherein the solid content of the polyurethane emulsion is 65-70%; Step 3: The polyurethane emulsion is mixed with ethyl acrylate, methyl methacrylate and methylenebisacrylamide to obtain a composite emulsion; the composite emulsion is divided into two equal parts, an initiator is added to one of the composite emulsions, the temperature is raised to 70-80°C, and the reaction is kept warm for 60-90 minutes to obtain a seed solution; the other composite emulsion is added to the seed solution and an initiator is added, the temperature is raised to 70-80°C, the reaction is kept warm for 30-60 minutes, and then the initiator is added continuously, the reaction is carried out at 80-85°C for 1-2 hours, and the temperature is lowered to obtain a polyurethane modified polyacrylate emulsion; in the composite emulsion, the content of each component, by weight percentage, is 55-65% of polyurethane emulsion, 20-35% of ethyl acrylate, 10-15% of methyl methacrylate, and 0.3-1% of methylenebisacrylamide; Step 4: The polyurethane modified polyacrylate emulsion is coated on one side of the PET film and baked to form an adhesive layer; the PET film is taken out, and a release film is applied on the surface of the adhesive layer to obtain an antistatic polarizer protective base film.

2. The method for preparing an antistatic polarizer protective base film according to claim 1, characterized in that: In step 1, sodium hydroxide is used to adjust the pH value to 8-8.

5.

3. The method for preparing an antistatic polarizer protective base film according to claim 1, characterized in that: In step 1, the amount of phosphoric acid used is 0.5-1% of the total weight of 3-dimethylamino-1-propylamine.

4. The method for preparing an antistatic polarizer protective base film according to claim 1, characterized in that: In step 1, the molar ratio of 3-dimethylamino-1-propylamine, 10-undecenoic acid and 1,3-dibromo-2,2-dimethylolpropane is 2:2:

1.

5. The method for preparing an antistatic polarizer protective base film according to claim 1, characterized in that: In step 2, the amount of each component used, by weight, is 40 to 48 parts of polytetramethylene glycol 2000, 30 to 36 parts of isophorone diisocyanate, 1 to 5 parts of 1,4-butanediol, 8 to 13 parts of dihydroxy quaternary ammonium salt, 5 to 8 parts of acetone, 4 to 6 parts of hydroxyethyl methacrylate, and 2 to 3 parts of acetic acid.

6. The method for preparing an antistatic polarizer protective base film according to claim 1, characterized in that: In step 3, the total amount of initiator used is 0.5-1.5% of the total weight of the reactants in the composite emulsion.

7. The method for preparing an antistatic polarizer protective base film according to claim 1, characterized in that: In step 4, the baking temperature is 110-120° C., the baking time is 2-5 min, and the thickness of the adhesive layer is 10-15 μm. 8 . The antistatic polarizer protective base film prepared by the preparation method according to claim 1 .

Citation Information

Patent Citations

  • Environment-friendly water-based laminating adhesive and preparation method thereof

    CN111777955A

  • Ultra-low stripping electrostatic voltage PU protective film and preparation method thereof

    CN112795330A

Cited By

  • Protective base film for polaroid and preparation method of protective base film

    CN121518048A

  • A protective base film for a polarizing plate and a method for producing the same

    CN121518048B

  • Intrinsic anti-static polarizer protective film base film and preparation method thereof

    CN121537664A

  • Essentially anti-static polarizer protective film base film and preparation method thereof

    CN121537664B